Transmigrasi Masyarakat Bali di Rama Dewa Tahun 1956 - Azahra, Fauzia; Karsiwan, Karsiwan (Yayasan Alpatih Harapan Semesta, 2023)
Lampung Province is one of the provinces in Indonesia that is the destination of transmigration, as well as a province inhabited by various tribes, one of which is Bali. This research uses qualitative approach method. This method uses data collection techniques that use 3 methods, namely observation, interviews, and documentation. The result of this study is that economic and demographic conditions became the driving factors that influenced the holding of the transmigration program of the Balinese people to Lampung in 1956. This transmigration process took place in Rama Dewa, Seputih Raman District. This was shown by the construction of the Transmigration Memorial monument of the Balinese people who came to Rama Dewa Village in 1956. The transmigration program is said to have been successfully motivated by findings that mentioned the success of the Balinese people in building life in Lampung since they first arrived in Lampung.